In situ observations on the habitat and abundance of the squat lobster Gastroptychus perarmatus (Haig, 1968) (Crustacea: Decapoda: Chirostylidae) in the n orthern Gulf of California, Mexico - Hendrickx, Michel E.; Hinojosa, Alejandro; Ayón-Parente, Manuel (Journal of threatened taxa, 2013)
Living specimens of Gastroptychus perarmatus (Haig, 1968), a chirostylid squat lobster, were observed on colonies of gorgonian corals and sponges in the northern Gulf of California. Video footage and photographs obtained from the Remotely Operated Vehicle JASON dive north of Angel de La Guarda Island in the northern Gulf of California indicate that this squat lobster lives on coral specimens of Callogorgia, probably C. flabellum (Ehrenberg, 1834), and on one or two unidentified species of sponge(s). Seven sites were observed to contain G. perarmatus with the number of individuals per host varying from 2 to 11. No specimens were observed on the sea floor away from a host. Review of videos indicates that most individuals of G. perarmatus observed remained motionless in the same position throughout the video recording period (max. 30 seconds), with the body erect and the chelipeds extended, presumably to facilitate collection of organic particles transported by the current. At one site, however, the video shows one adult specimen grasping large particles of floating debris retained on the gorgonian. Until recently there were no records of G. perarmatus since it was described from California in depths of 229m (north of Anacapa Island). A few specimens were accidentally captured in a benthic sledge in the northern Gulf of California in 2011. This is a new record for the area, including a new maximum depth record (705-710 m) for the species. This rare species of squat lobster and its host the gorgonian coral would be subject to severe environmental impacts if fishing or mining activities were developed in the area.